Nanocurcumin in myocardial infarction therapy: emerging trends and future directions - Lv, Mei; Sun, Qing; Yu, Yilin; Bao, Jinwei (Frontiers in Bioengineering and Biotechnology, 2025)
Myocardial infarction (MI) is the leading cause of morbidity and mortality worldwide. Curcumin has been observed to significantly reduce pathological processes associated with MI. Its clinical application is limited due to its low bioavailability, rapid degradation, and poor solubility. Advancements in nanotechnology can be used to enhance its therapeutic potentials in MI. Curcumin nano-formulation enhances its solubility, stability, and bioavailability, allowing more precise delivery to ischemic cardiac tissue. Curcumin nanoparticles have been observed to successfully reduce infarct size, maintain heart function by modulating essential molecular pathways in MI. Its liposomal formulations provide sustained release and higher tissue penetration with improved pharmacokinetics and enhanced therapeutic efficacy. Preclinical studies revealed that nanocurcumin drastically lower oxidative stress indicators, inflammatory cytokines, and cardiac damage. Micelles composed of polymers have demonstrated high biocompatibility and targeting capabilities with increased cardio-protective effects. Research and clinical trials are essential for comprehensive analysis and efficacy of curcumin-based nano-therapeutics in cardiovascular condition and lowering risk of MI.